Cloud effective transmittance at two sites of the Atacama Desert, Chile - Luccini, Eduardo Alfredo (2011)
Broadband overcast cloud effective transmittance was determined at Arica (18.47S, 70.31°W, 20 m above sea level (asl)) and Poconchile (18.45°S, 70.07°W, 560 m asl), Atacama Desert, northern Chile, from 10 min averaged pyranometer measurements of total solar irradiance (ToSI) and ultraviolet solar irradiance (UVSI) during the period 2002-2005. The predominant cloud type is marine stratocumulus, characteristic of the southeastern Pacific tropical environment. The region's very regular climate conditions, characterized by overcast mornings and cloudless afternoons, allow the application of an empirical method to determine the expected clear-sky irradiance during cloudy mornings. The cloud effective transmittance (CET) is determined as the ratio of the measured cloudy-sky irradiance over the expected clear-sky irradiance. CETTo = 0.26 (0.31) for ToSI and CETUV = 0.37 (0.43) for UVSI characterize overcast cloudiness at Arica (Poconchile). One-dimensional radiative transfer model calculations in both ToSI and UVSI ranges are also used. The measured and modeled relationships between CETTo and CETUV closely agree. New insights are given to explain the sparsely populated data around CET = 0.8 observed also by other similar studies.